Initial Multicenter Experience With a Novel Self-Expanding TAVR System in Patients With Aortic Valve Stenosis - Tamm, Alexander R.; Wienemann, Hendrik; Treede, Hendrik; Geyer, Martin; Arnold, Martin; Marwan, Mohamed; Theiss, Hans; Braun, Daniel; Bleiziffer, Sabine; Goncharov, Arseniy; Kuhn, Elmar; von Bardeleben, Ralph Stephan; et al. (Jacc-Cardiovascular Interventions, 2025)
Background: As transcatheter aortic valve replacement is performed increasingly in younger, low-risk patients, the need for commissural alignment and coronary access has increased. Design elements of the JenaValve Trilogy (JVT) transcatheter heart valve (THV) ensure both. Objectives: This study sought to evaluate the outcome of patients with aortic stenosis (AS) treated with this novel transfemoral, self-expanding THV. Methods: We included 43 consecutive patients with severe AS treated with the JVT system at 5 German sites. The primary endpoint of the study was technical success of the procedure. Procedural outcomes, hemodynamic valve performance, and clinical outcomes at 30 days were evaluated according to the Valve Academic Research Consortium-3 criteria. Results: The median age was 81 years (Q1-Q3: 77.0-83.9 years) with a median Society of Thoracic Surgeons Risk Score of 3.1% (Q1-Q3: 2.1%-5.9%). Technical success was achieved in 98% (n = 42 of 43). One patient was converted to open surgery. The median aortic gradient was 5.0 mm Hg (Q1-Q3: 4.0-7.0 mm Hg), and no patient had moderate or greater paravalvular regurgitation (88% [n = 37 of 42] with none or trace paravalvular regurgitation). At 30 days, major vascular complications and stroke each occurred in 1 (2.3%) patient, 2 (4.7%) patients had died, and permanent pacemaker implantation was needed in 4.9% (n = 2 of 41). Overall, early safety at 30 days was achieved in 82% (n = 27 of 33) of patients. Conclusions: Treatment of AS patients with this novel transfemoral THV system is safe and effective. The JVT offers an excellent alternative to established transcatheter aortic valve replacement prostheses for patients with AS.
CRIS-Team Scopus Importer:2025-01-31
Keywords: aortic stenosis; commissural alignment; paravalvular regurgitation; permanent pacemaker implantation; TAVR; trilogy